2006
DOI: 10.1177/0486613405283319
|View full text |Cite
|
Sign up to set email alerts
|

Cashing in on Shame: How the Popular “Tradition vs. Modernity” Dualism Contributes to the “HIV/AIDS Crisis” in Africa

Abstract: Orthodox descriptions and treatment of Africa's HIV/AIDS crisis are subject to robust controversy among research experts and clinicians who raise questions about the tests used to define the crisis, the statistics used to document the crisis, and the drugs marketed to curtail it. Despite this critical scientific corpus, fanciful misconceptions about chronic illness and mortality in Africa are sustained by ahistorical and apolitical analyses misrepresenting Africans' contemporary morality, social reality, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Historically, there have been reports of a cornucopia of infections which have left heavy scars on the world and domestic economies. Major research in mainstream disciplines in Economics and related fields have widely reported the economy of nations at different epochs with specific reference to diseases and outbreak of epidemics (See; Levenstein and Tuminaro, 1992 , Dixon et al, 2002 , Harrison, 2006 , Lauer, 2006 , Obeng-Odoom and Bockarie, 2018 , Jordà et al, 2020 ). Similarly, during the outbreak of COVID-19 in Wuhan, in China, since December 2019, economists and pundits equally made attempts to predict the present, medium and long-term effects of the pandemic on economies of nations using more sparse data ( Jordà et al, 2020 ; Wenham et al, 2020 ; Obeng-Odoom, 2020 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Historically, there have been reports of a cornucopia of infections which have left heavy scars on the world and domestic economies. Major research in mainstream disciplines in Economics and related fields have widely reported the economy of nations at different epochs with specific reference to diseases and outbreak of epidemics (See; Levenstein and Tuminaro, 1992 , Dixon et al, 2002 , Harrison, 2006 , Lauer, 2006 , Obeng-Odoom and Bockarie, 2018 , Jordà et al, 2020 ). Similarly, during the outbreak of COVID-19 in Wuhan, in China, since December 2019, economists and pundits equally made attempts to predict the present, medium and long-term effects of the pandemic on economies of nations using more sparse data ( Jordà et al, 2020 ; Wenham et al, 2020 ; Obeng-Odoom, 2020 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Alleviating unsanitary conditions would have beneficial effects on other diseases that exacerbate HIV/AIDS, such as malaria. Improving sanitary conditions such as sewage and garbage disposal eliminates breeding grounds for the mosquito that acts as a vector for malaria (Lauer, 2006). Making nutritional changes in a population is feasible and affordable.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in mortality rates of young women born during the 1983 famine in Ghana was witnessed starting in 2002. This trend could be explained by a possible latent effect of perinatal hunger on the functioning of the immune system that puts women at an increased risk of contracting HIV later in life when they have reached sexual maturity (Lauer, 2006). To the best of the author's knowledge, this possibility has yet to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…This is how Uganda overcame its national AIDS crisis: validating its latent, indigenous forms of democratic process. Abstinence lectures and condom distribution exercises were the least of it, something of a sideshow (Lauer, 2006). 21 From within African primordial publics, elected governments of the central state appear epiphenomenal.…”
Section: Democracy In Hidingmentioning
confidence: 99%